Characteristics of H2S emission from aged refuse after excavation exposure. (1st May 2015) - Shen, Dong-Sheng; Du, Yao; Fang, Yuan; Hu, Li-Fang; Fang, Cheng-Ran; Long, Yu-Yang
Abstract: Hydrogen sulfide (H2 S(g) ) emission from landfills is a widespread problem, especially when aged refuse is excavated. H2 S(g) emission from aged refuse exposed to air was investigated and the results showed that large amounts of H2 S(g) can be released, especially in the first few hours after excavation, when H2 S(g) concentrations in air near refuse could reach 2.00 mg m −3 . Initial exposure to air did not inhibit the emission of H2 S(g), as is generally assumed, but actually promoted it. The amounts of H2 S(g) emitted in the first 2 d after excavation can be very dangerous, and the risks associated with the emission of H2 S(g) could decrease significantly with time. Unlike a large number of sulfide existed under anaerobic conditions, the sulfide in aged municipal solid waste can be oxidized chemically to elemental sulfur (but not sulfate) under aerobic conditions, and its conversion rate was higher than 80%. Only microorganisms can oxidize the reduced sulfur species to sulfate, and the conversion rate could reach about 50%. Using appropriate techniques to enhance these chemical and biological transformations could allow the potential health risks caused by H2 S(g) after refuse excavation to be largely avoided. Highlights: The initial air exposure can promote H2 S emission from aged refuse. H2 S could be reduced effectively within a few days after air exposure. Sulfide could be oxidized chemically to sulfur in landfill after excavation.